Islamic Ethical Leadership: Improving the Performance of Sharia Financial Institutions with CSR during the Covid 19 Pandemic - Muhammad Trihudiyatmanto; Dian Asmarajati (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
AbstractPurpose - This research was conducted with the aim of identifying the relationship between Islamic Ethical leadership on organizational performance with social responsibility as a mediation moderated by the covid 19 pandemic.Method - The research data were obtained from BMT Al-Amin located in Wonosobo Regency, Central Java Province. Samples were taken from the population using census sampling. Data collection is taken directly from the object of research through a questionnaire. Then the data were analysed by Structural Equation Modelling (SEM) with Amos software version 20.Result - From the research that has been done, it is found that Islamic Ethical leadership has an effect on organizational performance at BMT Al-Amin. CSR apparently does not mediate the relationship of Islamic Ethical leadership to organizational performance. And the COVID-19 pandemic has also not moderated CSR's relationship to organizational performance.Implication - This study uses data on BMT Al-Amin, Wonosobo Regency, Central Java Province.Originality- This paper looks at the relationship of ethical leadership to organizational performance with social responsibility as a mediation moderated by the covid 19 pandemic in order to support the creation of BMT growth in Wonosobo Regency during the covid 19 pandemic which is influenced by ethical leadership attitudes through CSR.